Clinicopathologic and Genomic Characterization of PD‐L1 Positive Urothelial Carcinomas. (25th March 2021) - Huang, Richard S.P.; Haberberger, James; Harries, Lukas; Severson, Eric; Duncan, Daniel L.; Ferguson, N. Lynn; Hemmerich, Amanda; Edgerly, Claire; Murugesan, Karthikeyan; Xiao, Jinpeng; McEwan, Deborah; Holmes, Oliver; et al.
Abstract: Introduction: Pembrolizumab was approved with an accompanying companion diagnostic (CDx) assay (PD‐L1 DAKO 22C3) for urothelial carcinoma (UC). In this study, we further characterize the clinicopathologic and genomic features of UC that are programmed death‐ligand 1 (PD‐L1) positive. Materials and Methods: The cohort of this study consisted of a total of 528 consecutive UC patients with PD‐L1 immunohistochemistry (IHC) and comprehensive genomic profiling (CGP). All PD‐L1 IHC testing was performed using the DAKO 22C3 CDx assay for UC. PD‐L1 positivity was determined at a combined positive score ≥ 10. Results: A total of 44.5% (235/528) patients with UC were PD‐L1 positive . A lower PD‐L1 positivity rate was detected in primary (42.3%, 148/350) versus metastatic sites (48.9%, 87/178). PD‐L1 positivity was dependent on the location of the metastatic sites. CGP revealed PD‐L1 positive patients had more frequent genomic alterations (GAs) in TP53 ( p = .006) and RB1 ( p = .003) and less frequent GAs in FGFR3 ( p = .001) and MTAP ( p = .028). The APOBEC mutational signature and tumor mutational burden (TMB)‐high were more common in PD‐L1 positive patients. By testing patients with UC with CGP, in addition to PD‐L1 IHC, an additional 97 patients (18.4%) in the total cohort were eligible for immunotherapy based on TMB status. Conclusion: PD‐L1 positive and PD‐L1 negative urothelial carcinomas are genomically different. Also, our study provides the framework for future clinical investigation with regard to specimen site selection for PD‐L1 testing as well as candidate biomarker genomic alterations that may predict for better response or lack of response to immune checkpoint inhibitors. Implications for Practice: In this study, a higher prevalence of TP53 and RB1 alterations and APOBEC mutational signatures in the PD‐L1 positive urothelial carcinoma disease subset and enrichment of FGFR3 alterations in the PD‐L1 negative disease subset were found. These data provide the basis for future investigation into the role of these genomic changes as positive and negative predictors of immunotherapy response. Also, differences wer seen in PD‐L1 positivity based on the collection site of the sample, which can provide a framework for future clinical trial design and could influence sample selection for PD‐L1 testing in patients with urothelial carcinoma when multiple samples are available. Abstract : This study evaluated 528 patients with urothelial carcinoma and provides insight into the genetics and clinical features that distinguish PD‐L1 positive and PD‐L1 negative tumors.